2021
DOI: 10.1371/journal.pone.0259782
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of postpartum depression among postpartum mothers in Kuala Lumpur, Malaysia: A cross-sectional study

Abstract: Postpartum depression (PPD) is one of the mental health complications that may arise following childbirth. This cross-sectional study explores the association between socioeconomic factors and PPD literacy with PPD incidence in 350 participants (mean age: 30.58±4.72 years) at one to six months postpartum, who attended the Kuala Lumpur Health Clinic from May to October 2020. PPD incidence and literacy were assessed using the validated Malay versions of the Edinburgh Postpartum Depression Scale (EPDS) and the Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
2
6
0
2
Order By: Relevance
“…Results of this study painted a preliminary picture of the level of PoDLi in perinatal women in China. The findings suggested that the PoDLi level (3.80 ± 0.38) among Chinese perinatal women was in the moderate range, which was very close to the findings in the Iran (3.79 ± 0.39) (Mirsalimi et al, 2020) and Malaysia (3.78 ± 0.37) (Hairol et al, 2021) samples, and a study in India (Poreddi et al, 2021) showed that only half of postpartum mothers had adequate levels of PoDLi. Consequently, there is an imperative need, both in China and many other developing countries, to sensitize perinatal women about PPD via various approaches such as presenting knowledge of PPD in community campaigns and pregnancy schools, thereby creating awareness of PPD and improving helpseeking behaviors.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Results of this study painted a preliminary picture of the level of PoDLi in perinatal women in China. The findings suggested that the PoDLi level (3.80 ± 0.38) among Chinese perinatal women was in the moderate range, which was very close to the findings in the Iran (3.79 ± 0.39) (Mirsalimi et al, 2020) and Malaysia (3.78 ± 0.37) (Hairol et al, 2021) samples, and a study in India (Poreddi et al, 2021) showed that only half of postpartum mothers had adequate levels of PoDLi. Consequently, there is an imperative need, both in China and many other developing countries, to sensitize perinatal women about PPD via various approaches such as presenting knowledge of PPD in community campaigns and pregnancy schools, thereby creating awareness of PPD and improving helpseeking behaviors.…”
Section: Discussionsupporting
confidence: 80%
“…It will be beneficial to conduct rasch analysis based on the non-parametric item response theory in future research, which allows conclusion to be drawn independently from the tested population (Nguyen et al, 2022), to provide additional important information on C-PoDLiS psychometric properties. Third, it is difficult for us to adequately compare our findings with the other relevant studies (Mirsalimi et al, 2020;Hairol et al, 2021;Poreddi et al, 2021) for the reason that, except for the study of developing the original version of PoDLiS (Mirsalimi et al, 2020), none of the others (Hairol et al, 2021;Poreddi et al, 2021) had performed formal evaluation of the psychometric properties of PoDLiS with Cronbach's α reported only. As such, future studies need to evaluate and report the psychometric properties of the PoDLiS formally, which can enable the comparison between different versions of the PoDLiS and promote the popularization of the scale internationally.…”
Section: Frontiers Inmentioning
confidence: 88%
See 2 more Smart Citations
“…To avoid and/or mitigate this, there is a need to strengthen the supportive bonds, restore sleep and rest, and provide psychotherapeutic treatment using a cognitivebehavioural approach [70]. No relationship was observed between the number of children, ethnicity, women's education, and puerperal depressive symptoms [71].…”
Section: Discussionmentioning
confidence: 99%